Value, capital and nature: some ecological implications of Marx's critique of political economy - Burkett, Paul (1996)
Marx's critique of political economy is interpreted in terms of the contradiction between: (1) the necessary role of nature, along with labor, as a source of use value; (2) value's representation of wealth by the abstract labor time objectified in commodities. Capitalism's tendency to despoil its natural environment is constituted in the basic relation of capitalist exploitation and the corresponding value form of the products of labor and nature. Marx's analysis thus provides the basis for a coherent historical specification of capitalism's natural conditions and limits - one that organically relates ecological and class struggles while highlighting the need for alternatives to the market in order to achieve ecologically sustainable production - Reproduced
Keywords: Marx on political economy